3D solvent-free energetic metal–organic framework (EMOF) achieved by removing inclusion molecules from a new coordination polymer. Issue 4 (3rd January 2019) - Zhang, Sheng; Wu, Shuo; Zhang, Wendou; Yang, Qi; Wei, Qing; Xie, Gang; Chen, Sanping; Gao, Shengli; Lu, Jack Y.
Abstract : The reaction of CuCl and NaN3 with 4, 4′-azo-1, 2, 4-triazol-5-one (H2 ZTO) under solvothermal conditions produced a new 3D heteronuclear Cu(i )-Na(i ) energetic metal–organic framework (EMOF), [Cu3 Na(ZTO)2 ] n · n CH3 CN (1 ). Abstract : The reaction of CuCl and NaN3 with 4, 4′-azo-1, 2, 4-triazol-5-one (H2 ZTO) under solvothermal conditions produced a new 3D heteronuclear Cu(i )-Na(i ) energetic metal–organic framework (EMOF), [Cu3 Na(ZTO)2 ] n · n CH3 CN (1 ). Compound1 underwent a heating–desolvation process that resulted in a new stable solvent-free EMOF, [Cu3 Na(ZTO)2 ] n (2 ), with a nitrogen content of 37.22%. The heat of detonation found for compounds1 and2 were 1.67 kcal g −1 and 1.71 kcal g −1, respectively. Compound2 exhibits a higher thermal stability, and is insensitive to external stimuli. The non-isothermal kinetic and apparent thermodynamic parameters for the exothermic decomposition process of2 were determined using Kissinger's and Ozawa's methods.